República Dominicana. Logros significativos 2010-2017 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in the Dominican Republic are identified, during the period from 2010 to 2017, with respect to the needs and interests of the country, strengthening issues such as beekeeping, aquaculture, innovation, technologies, exports, use of pesticides, food security, organic agriculture, waste management and resilience against climate change. Likewise, work was done to improve the production of fish, silvopastoral, cattle and milk, the agricultural sector and to support small and medium-sized ranchers. Finally, technical assistance was provided in the use of international quarantine and in improving the value chains of honey, rice, chayote and raspberry.